Fatores contingenciais e sua relação com a utilização de artefatos para análise do custo de concorrentes: um estudo de casos múltiplos - Friedrich, Laercio Rogerio (Universidade do Vale do Rio dos Sinos, 2019)
This thesis investigates the relationship between contingency factors and the use of artifacts for the competitive cost analysis, through a multiple case study. The competitive cost analysis within the context of strategic cost management arose from the recognition that, although being relevant, the traditional cost accounting is not sufficient for decision making. Therefore, it has turned its attention to external factors and aligned its purpose to the premises of contingency theory, which assumes the need for adjustment between the organizational structure and the internal and external contingent factors to the organization. This qualitative research had the primary data collected through semi-structured interviews, carried out along the second semester of 2018, with managers of strategic areas. Three companies from different business lines participated in the study: Móveis Castro Ltda, in the furniture business; Germani Alimentos Ltda in the food business.; and Imply Tecnologia Eletrônica Ltda. in the technology and entertainment business. The secondary data were observed and collected from the web portals of the companies, associations, unions, as well as websites and other relevant virtual media. As for the outcomes: among the three companies, three of the seven following artifacts were featured as predominant incidence in the managers’ everyday practices: strategic pricing; reverse engineering and; benchmarking. The findings indicate that the artifact tends to be shaped by the factors influence, which adapts according to the managers needs for decision making. Through the artifacts use, the study reveals that, to a certain extent, the environmental factor precedes other factors, which means that the company adapts to its environment in order to optimize other factors, such as strategy, structure and technology in relation to the use of artifacts that depends mostly on the business field, organizational characteristics and the market.
Keywords: Artefatos para análise do custo de concorrente; Custo de concorrentes; Fatores contingenciais; Gestão estratégica de custos; Artifacts for competitor cost analysis; Competitive cost; Contingency factors; Strategic cost management; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis